(untitled) - Albright, William Foxwell (ed.); Freedman, David Noel (ed.); McCarter, P.Kyle (New York, 1984)
.AB: Map-1:Hebron and the surrounding area including Ziklag; , Map-2:The claims of Ishbaal; , Map-3: Jerusalem and the Mount of Olives in the time of David; , Map-4:David's Philistine wars; , Map-5:David's Empire;, Map-6: David's Ammonite-Aramean War, Map-7: Abishalom's Revolt, Map-8: Sheba's Revolt, Map-9: Homes of David's Warriors, Map-10: David's Census
No.9
Keywords: Freedman, David Noel (ed.); Bible Old Testament - Samuel; McCarter, P.Kyle